The Role of Word-Of-Mouth, Shopping Lifestyle and City Walk Concept on Brand Image Mall in Indonesia - Wiyanti, Sari; Hanfan, Ahmad (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
ABSTRACT After 2 years of going through the covid-19 pandemic, now malls or shopping centers can operate normally. Economic growth in Tegal is quite high, changing people's lifestyles and consumption behavior. The consumerism character of the people of Tegal has an impact on the high purchasing power and circulation of money. The fairly high competition does not discourage mall and retail business players from competing competitively. People will look for shopping places that provide comfort, magnificent buildings, exterior and interior form a good image of a mall. This study uses a randomized quantitative approach with the population being Mall visitors in Tegal. The number of samples taken in this study were 100 respondents. The sampling technique used was purposive sampling, namely samples that were met by chance and met the criteria in this study. The research data was obtained through questionnaires distributed and filled in by the respondents, which would then be processed with SPSS 22. The results of this study found that